2011
DOI: 10.1007/s12253-010-9336-9
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12 and ADAM17 Gene Expression in Laser-capture Microdissected and Non-microdissected Breast Tumors

Abstract: ADAM (a disintegrin and metalloprotease)12 and ADAM17 are multidomain transmembrane proteins involved in ectodomain shedding of cytokines, growth factors and adhesion molecules, with pivotal activities in the tumor microenvironment. The aim of this study was to confirm the up-regulation of ADAM17 and ADAM12 gene splicing variants in breast tumors and to delineate their expression between laser-capture microdissected (LCM) and non-microdissected breast tumors. The gene expression was analyzed by quantitative-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…ADAMs, a subfamily of the matrix metalloproteinases, have generated much interest in the last several years and participate in a number of cellular processes, including adhesion, extracellular matrix degradation, migration, and proliferation, processes which are important in the carcinogenesis sequence. Increased ADAM12 expression has been found in human carcinomas of the liver , bladder , breast , larynx , and lung . ADAM12 is also highly expressed in carcinoma‐associated stroma and is necessary for prostate tumor progression in mouse models .…”
Section: Discussionmentioning
confidence: 99%
“…ADAMs, a subfamily of the matrix metalloproteinases, have generated much interest in the last several years and participate in a number of cellular processes, including adhesion, extracellular matrix degradation, migration, and proliferation, processes which are important in the carcinogenesis sequence. Increased ADAM12 expression has been found in human carcinomas of the liver , bladder , breast , larynx , and lung . ADAM12 is also highly expressed in carcinoma‐associated stroma and is necessary for prostate tumor progression in mouse models .…”
Section: Discussionmentioning
confidence: 99%
“…Although the retrograde fluorescence labeling and Nissl staining complicated the microdissection and RNA extraction, our study showed that the total RNA from the two different FMNs could be effectively used for gene expression analysis by real‐time qRT‐PCR. Previous studies successfully used partially degraded input RNA with a low RIN for gene analysis . Furthermore, as we had hypothesized before the study, in the dormant and reinnervating FMNs, gene expressions of multiple ionotropic glutamate receptor subunits were different 90 days after facial‐facial anastomosis.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies successfully used partially degraded input RNA with a low RIN for gene analysis. [19][20][21] Furthermore, as we had hypothesized before the Prior studies examined the mRNA expression of ionotropic glutamate receptor subunits in the whole facial nucleus region. Nevertheless, detecting and sampling processes, including the manual collection of specimens, in situ hybridization, or regular RT-PCR, would unavoidably affect the reproducibility of results and thereby decreased the power of a study.…”
Section: Discussionmentioning
confidence: 99%
“…However, only ADAM12 is overexpressed in benign non-LCM tumor samples. The differences between LCM and non-LCM tumor samples were due to the influences of stroma on theses markers expression [ 57 , 94 ].…”
Section: Adams In Breast Cancermentioning
confidence: 99%
“…It is also termed as TACE (TGF-α converting enzyme) [ 58 ],since, it was originally recognized by its capability to cut off membrane bound TNF- α from its progenitor [ 97 , 59 ]. ADAM17 is the main sheddase for HB-EGF, TGF-α, epiregulin, and amphiregulin [ 57 , [60] , [61] , [62] ] and it was demonstrated to be elevated in human breast carcinomas [ 97 ]. ADAM17 is also implicated in several biological procedures and cleaves plenty of substrates such as TNF-α, TNF receptor, CD40, EGF receptor L, c-kit, p75NTR, c-fms, interleukin-1 receptor, interleukin-6 receptor growth hormone receptor, L-selectin, MUC1, vascular cell adhesion molecule-1, collagen VII, CX3CL-1, Notch, prion protein, and β-amyloid precursor [ 59 , [63] , [64] , [65] ].…”
Section: Adams In Breast Cancermentioning
confidence: 99%